Características clínicas e epidemiológicas de 146 pacientes com esclerose múltipla acompanhados na cidade de Fortaleza, CE, Brasil, entre os anos 1979 e 2010 - Teixeira, Carlos Augusto Ciarlini (2011)
In order to study the natural history of Multiple Sclerosis (MS) in the state of Ceará, Brazil, the author retrospectively analyzes 146 patients diagnosed according to Poser and/or McDonald-2010 criteria. Cases and methods: biographical, clinical and para-clinical data collected on outpatient visits and at relapses. EDSS scores 4, 6 and 7 used as disability outcomes. Statistical software R (RKWard 0.5.3) used to perform descriptive analysis, Fisher exact test (p< 0,05) and time-to-the-event curves (Kaplan-Meier). Results: over 75 % of the patients followed for as long as 15 years; disease onset before 30 years of age in 47,9 %, with female sex preponderance (80.82 %). Patients with university education (33,5 %) are in high proportion when compared to the general population. Sensory, motor and sphincter complaints are the most common, in both initial and final examinations. Younger patients with relapsing-remitting MS took a longer time to reach EDSS 4. The proportion of benign MS cases was 4, 7 %. Annualized relapse rate was 0,6 . For most patients, the first two relapses took place in the initial three years of illness.Time between 1st. and 2nd relapses bears a positive relationship with time to reach EDSS 4, 6 and 7. Disease duration until death (8 cases , 5,4 %) was an average of 14,4 years. The prevalence of MS in the state of Ceará, Brazil, is estimated as 2,9 / 100.000 inhabitants. Conclusion: Clinical course of MS in the state of Ceará, Brazil (south latitudes between 2o 46’ and 7o 52’ ) is similar to that observed worldwide.